Nigeria during the Abacha Years (1993-1998) - (:unkn) unknown (My University, 2001)
The autocratic regime of Sani Abacha (1993-1998) stands out as a watershed in the history of independent Nigeria. Nigeria’s darkest years since the civil war resulted from his unrestrained personal rule; very close to the features associated with warlordism. Nepotism, corruption, violation of human rights, procrastination over the implementation of a democratic transition, and the exploitation of ethnic, cultural or religious identities, also resulted in the accumulation of harshly repressed frustrations. In this book, some distinguished scholars, journalists and civil society activists examine this process of democratic recession, and its institutional, sociological, federal and international ramifications. Most of the contributions were originally presented at a seminar organized by the Centre d’Etude d’Afrique Noire (CEAN) in Bordeaux.
Keywords: African Research